PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) BERBASIS KEWIRAUSAHAAN UNTUK PROYEK KARTU MENU INFORMASI GIZI BUAH - Sari, Richa Purmaya; Adlim, Muhammad; Gani, Abdul; Akmalia, Nur (Lantanida Journal, 2025)
The absence of worksheets that can encourage students' entrepreneurial spirit and promote the process of activity is one of the difficulties in implementing STEM education. The purpose of this study is to provide Student Worksheets (LKPD) for menu card projects that include details on the nutritional value of fruit and are based on Science, Technology, Engineering, and Mathematics (STEM). The research and development technique is used in this study. The analysis, design, development, implementation, and evaluation phases are all included in the ADDIE development framework. Nevertheless, this article is restricted to the stage of development. A needs analysis questionnaire and a LKPD product quality assessment sheet were used as instruments for data collection. The findings demonstrated that the average scores for the expert validity evaluation of LKPD for face validity and content validity were 92.5% and 90%, respectively. With a very valid category, the overall validation result for the STEM-based LKPD combined with entrepreneurship is 91.25%. Consequently, experiments can be conducted using the created LKPD.